PENGARUH MODEL PEMBELAJARAN ADVANCE ORGANIZER TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN AL-QUR’AN HADIST KELAS V MI MUHAMMADIYAH 07 SUGIHAN SOLOKURO LAMONGAN TAHUN PELAJARAN 2023/2024 - Rafuhal Aisy' Faizah dan Idzi' Layyinnati (STIT Muhammadiyah Paciran, 2024)
Abstrak: Education plays an important role in human life. In learning a teacher's understanding of the model and mastery of the learning material will affect the way they teach, therefore the researchers use the learning model Advance Organizer to apply to the subjects of Al-Qur'an Hadits material surah al-humazah at MI Muhammadiyah 07 Sugihan because this learning model is considered suitable for researchers to be applied in the classroom, this research uses quantitative research with a parametric statistical approach. The one group pre test posttest. The subject of the research here is a student of grade V mi Muhammadiyah 07 sugihan which has a total of 24 students, in this study, the researchers use documentation methods and tests as data collection techniques. The result of the application of the Advance Organizer model to the student's learning outcomes in MIM 07 Sugihan with a total pretest of 9 students declared to be successful with a presentation of 37.5% and posttest data increased with the presence of 13 students indicated to be happy with a presentation of 54.1%. At the correlation result obtained a ratio of 0.906 with a very strong category and rtable with the number of respondents 24 at a significant level of 0.05 by 0.4004. This shows that rhitng>rtabel (0.906>0.4004). Based on the significant test results above obtaines a score of 10,021 and a table with a number of replies 24 on a significant average level of a = 0.05 and dk = the total respondents obtains 2,047. Then it can be concluded that thitung>ttable (10,021>047). Then the data is declared significant. This means that an 82% increase in student learning outcomes is influenced by the Advance Organizer learning model, while the rest is affected by other factors not examined in this study.